THE ROLE OF NGO’s IN STRENGTHENING THE FARMER GROUPS (RESEARCH ON THE ROLE OF MERCY CORPS INDONESIA IN HUMBANG HASUNDUTAN DISTRICT) - Hendrik Sitanggang; R.Hamdani Harahap; Abdul Kadir (Dinasti Publisher, 2021)
One of the problems in agriculture is the institutional problem of farmers who are not supportive. Non-Governmental Organizations can take a role in strengthening farmer groups, especially people in agricultural areas such as Humbang Hasundutan District. The purpose of this research is expected to provide in-depth information to describe and analyze activities conducted by Mercy Corps Indonesia in strengthening farmer group institutions. Research on the role of non-governmental organizations in instutional strengthening farmer group. This research uses qualitative methods. Researchers function as data collectors and analyzers related to the role of Mercy Corps Indonesia's non-governmental organizations in institutional strengthening farmer groups in Sinambela village at Humbang Hasundutan District. The results of this research were concluded several things, such as 1) Mercy Corps Indonesia Non-Governmental Organizations take a role in group strengthening farmers in Sinambela village, among them was through Livehood activities such as outreach activities, field meetings, making GAP (Good Demostration Practices) demonstration plots and strengthening the organization of farmer groups in Sinambela village. 2) Saolan and Haluaon farmer groups are slowly starting to strengthen from the dimension of organizational, human resources, finance, infrastructure and cooperation.